Competing Narratives of Victimhood and Aggression: Japanese Memory of Wartime in Sakae Tsuboi’s Nijushi No Hitomi - Aminah, Shobichatul (UI Scholars Hub, 2019)
The conclusion of the Pacific War witnessed the emergence of contradictory narratives that soon competed for ownership of Japan’s official wartime memory. As ardent nationalism was replaced with pacifism and a global outlook, Japan’s total military defeat was largely refigured into a narrative of victimhood. Simultaneously, the aggression of the past was purposefully downplayed. Pacifism is enshrined in the Article 9 of Japan’s Constitution. That clause represents a cherished part of the country’s postwar identity. This study investigates the memory of war as described in Sakae Tsuboi’s novel, Nijushi no Hitomi, that depicts the lives of a teacher’s and her 12 students in a hamlet on Shodo Island who experienced the Pacific War. Using Sakae’s novel as a lens, this paper considers Japanese memory of war with from the dialectic of the nationalistic spirit propagated during the war and the later commitment to pacifism. Employing the narrative discourse theory proposed by Genette, the narration of war memory is explored through the analysis of the actions and events surrounding the characters in the text. Narrative voices in the text are examined to reveal the perspective of each character in forming different memories of the war. The memories of war are discussed based on Hashimoto Akiko's theory which proposed that there are three kinds of Japanese memories about the war; i.e as a hero, as a victim and as a perpretator. This paper shows that there are two kinds of narrative in the Japanese memory related to war: i.e memory of victimhood and heroism. Memories of victimhood provoked trauma which in part gave rise to the Japanese commitment toward pacifism. At the same time, memories of heroism can lead to unvarnished nationalism, with can still cause the commitment to pacifism to waver.